ANALISIS KEHILANGAN AIR PADA SALURAN SEKUNDER (STUDI KASUS DAERAH IRIGASI BENDUNG AIR NIPIS BENGKULU SELATAN) - Hasnul Efendi; Muhammad Ali; Rena Misliniyati (Universitas Bengkulu, 2019)
The objectives of this research was to analyze how much the loss of irrigation water that occured in secondary channel at the irrigation area of Air Nipis Dam, South Bengkulu. Water losses were analyzed by using the method of debit in and out. The primary data were flow velocity, water depth, and cross section. In addition to primary data also used secondary data. They were temperature, wind speed, and humidity obtained from the Meteorology, Climatology and Geophysics Departement of Bengkulu. This research analyzed how much effect the percentage of water loss due to seepage and evaporation. From analysis calculations obtained the percentage of water loss value due to seepage and evaporation was not too significant. it can be concluded based on the observation of most water loss occurs due to the other factors, such as leaks in the lines, wild plant vegetation along the channel, etc. The results of this research showed that the percentage of total water loss value occurred on channel BN Kr 4 of 85,40% for the left secondary channel and channel BSB 1 of 74,16% for right secondary channels. While the value of the smallest percentage of total water loss occured in channel BN Kr 7 of 24,14% for the left secondary channel and channel BDA 1 of 22,53% for right secondary channels